Seasonal Dynamics of Sediment Microbial Communities at Different Distances from Artificial Reef Units - Meiling Zhu; Yanli Tang (Microorganisms, 2025)
Artificial reefs (ARs) are important for habitat restoration and exhibit clear spatial gradient effects. However, most studies focus on AR groups, neglecting the ecological functions and mechanisms of individual AR units at a local scale. This limits a deeper understanding and optimization of the ecological effects of ARs. This study employed high-throughput sequencing to examine the seasonal and spatial variations in sediment microbial communities surrounding AR units. The results showed that microbial community distributions in sediments varied significantly with seasons, reef distance, and reef structure. The community structure varied significantly across seasons at different reef distances, with the most unique structure observed at 3 m (1.5-times the reef height). In May, microbial community spatial changes were mainly driven by sediment organic matter (OM), while in November and February, although the spatial enrichment patterns of microbial groups changed seasonally, they were not strongly affected by functional types (aerobic or anaerobic). The Neutral Community Model (NCM) showed lower levels of R2 and Nm at 0 m and 3 m, which are relatively consistent with the flow field effects (upwelling and reverse eddy currents). Key environmental factors and their regulatory effects vary with distance from the reef.